A Pragmatic Analysis Of Directive Utterances Found In Holy Qur'an Chapter Al- Mu'minun - Saputri, Weni; , Drs. Sigit Haryanto,M.Hum (2017)
This research aims to indentifying the pragmalinguistics forms of directive utterances in Holy Qur'an chapter Al-Mu'minun and describing the intention of directive utterances in Holy Qur'an chapter Al- Mu'minun. This research is included into qualitative research. The data source of this research is directive utterances that found in Holy Qur'an. Technique of collecting data used observation and documentation method. The data were analyzed by using Blum-Kulka (1989) theory of commanding, House and Kasper (1989) theory of requesting, and Martine-Flor (2005) theory of suggesting analyzing the pragmalinguistics forms and Yule's theory to indentify the intention of directive utterances in this data. The writer found 45 data of directive utterances in Holy Qur'an Chapter Al-Mu'Minun. The result of this research shows that there are three types of pragmalinguitsics forms commanding, two types of pragmalinguitsics forms requesting and two types of pragmalinguitsics forms suggesting. The writer also found four types of directive utterances they are: 27 data or 60% of commanding utterances, 16 data or 36 % of requesting utterances,2 data or 4 % suggesting utterances. Keyword: directive utterances, Holy Qur'an, chapter Al-Mu'minun, pragmalinguitics forms, intention of utterance.